CLASSIFYING STROKE RECOVERY PROFILES BASED ON LIVING ENVIRONMENT: A LATENT CLASS ANALYSIS - Ozgun, M.; Akanyeti, O.; Povina, F. Villagra; Rahman, R.; Saybasili, H.; Atalar, D. (Sage Publications Ltd, 2025)
[Abstract Not Available]